Grafičko-analitičko modeliranje maksirnalnih manevarskih sposobnosti zrakoplova u horizontalnoj ravnini - Grozdanić, Berislav (Promet - Traffic&Transportation, 2012)
During the Croatian War the military forces of the RepublicofCroatia were faced both with foreseen and unforeseen demandsregarding successful airspace combat actions, requiringfull engagement of all human and physical resources of theCroatian Military Air Force.Military Air Force, the most sophisticated part of thearmed forces, has contributed to the success of the operationsby acting in and from airspace against ground and sea targets.The supersonic aircraft efficiency in combat action overairspace targets can be increased by acquiring knowledge regardingthe maximal maneuvering capabilities, application ofgraphic-analytic modeling during flight preparations, educationof pilots and other participants in order to maximally exploitthe aricraft capabilites applying the forced turn. Graphicanalyticmethod of preparing the pilot for combat mission isone of the methods used at a higher level of psychological, theoreticaland practical realizations of the next flight conditions.It is applied in order to increase the efficiency of air-combatand to reduce one's own losses.